Lack of Association between Promoter Gene Polymorphism (-318 C/T) and Multiple (Journal of Sciences, Islamic Republic of Iran)
Multiple sclerosis (MS), a chronic inflammatory demyelinating disease of the central nervous system is believed to have a T cell-mediated autoimmune etiology. The cytotoxic T lymphocyte antigen 4 (CTLA-4) gene is a strong candidate for the involvement in autoimmune diseases. To examine the genetic association of the CTLA-4 gene locus with MS, in a case-control design, we analyzed (-318 C/T) single nucleotide polymorphism of the CTLA-4 gene in 135 unrelated Iranian relapsing-remitting MS patients and 135 age, gender and ethnicity-matched healthy subjects using PCR-RFLP method. The frequency of CTLA-4 gene (-318) polymorphism among cases and controls was 52.1% vs. 47.9% for CC, 39.2% vs. 60.8% for TC and 75.0% vs. 25% for TT genotypes respectively. The distribution of CTLA-4 (-318 C/T) genotype and allele frequencies did not significantly differ between MS patients and healthy subjects. In conclusion, there may not be any association between CTLA-4 gene (-318 T/C) polymorphism and MS development.